Normal form of formulas of pure hybrid logic - Aleknavičiūtė, Daiva; Norgėla, Stanislovas (Lietuvos matematikos rinkinys, 2021)
In this paper,we study a transformationof pure hybrid logic formulae,which do not have binding operator, into an equivalent normal form, which does not have any satisfiability operators in the scope of another satisfiability operator.